Burnout y calidad de vida laboral en empresas públicas y privadas - Echegaray Luperdi, Ximena (2021)
Burnout is a negative psychological experience for the individual who suffers from it, since it involves problems, restlessness, annoyance, dysfunction and / or adverse consequences (Maslach, 2017). This syndrome causes wear and tear on the quality of professional life (Leonardo & Chocó, 2018), which directly affects the health and wellbeing of employees, in addition to the high cost it entails for organizations. The objective of this report is to know the relationship between burnout and the quality of working life in public and private companies. An applied review of scientific articles and quantitative theses was carried out following the guidelines of the PRISMA guide (Urrútia & Bonfill, 2010), in the Redalyc, ScienceDirect and ALICIA databases, and 7 full-text publications were considered. The main findings answer the research question, and show the close relationship between the variables involved. In general terms, a low number of scientific investigations on the subject was observed in the business field, which suggests the need to develop new longitudinal studies, both at the international and national level, and to evaluate and compare the behavior of the variables in the different occupational areas (health, education, organizational, others).